Magi. 10 : the labyrinth of magic. - Otaka, Shinobu (VIZ Media, 2015)
"Sent to explore the dungeon known as Zagan, Aladdin and his friends have arrived on Tran Island. The mysterious Tran people are reluctant to help Aladdin defeat the dungeon, and it's no wonder why-- the ancient labyrinth seems to have a mind of its own! Overcoming Zagan will bring Aladdin face-to-face with old adversaries and some powerful and dangerous new foes"--Page 4 of cover.